2021
DOI: 10.1155/2021/6650870
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Loop-Mediated Isothermal Amplification Assay as a Point-of-Care Tool for the Detection of Wuchereria bancrofti in Human Blood in Tana River Delta, Kenya

Abstract: Introduction. Accurate detection of filarial parasites in humans and vectors is essential for the implementation and evaluation of Global and National Programs to eliminate lymphatic filariasis. Immunological methods to detect infection are available; however, cross-reactivity issues have been reported in most of them. Nucleic acid-based molecular assays offer high levels of specificity and sensitivity and can be used to detect the infections. Methods. In this study, we evaluated loop-mediated isothermal ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…These can be avoided by adding dimethylsulfoxide (DMSO) to the reaction. De-Guo Wang et al (2015) and Kinyatta Nanc et al (2021) demonstrated that adding 7.5% of DMSO in the reaction mix improved the LAMP specificity [ 34 , 35 ].The potential benefit of the LAMP assays developed in this study is their ability to detect not only bacteria responsible for UTI but also the most common resistance to C3G antibiotics, the CTX-M group 1. The early diagnosis of this gene could lead to improving the antibiotic therapy and antimicrobial stewardship (Additional file 1 , Additional file 2 , Additional file 3 , Additional file 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…These can be avoided by adding dimethylsulfoxide (DMSO) to the reaction. De-Guo Wang et al (2015) and Kinyatta Nanc et al (2021) demonstrated that adding 7.5% of DMSO in the reaction mix improved the LAMP specificity [ 34 , 35 ].The potential benefit of the LAMP assays developed in this study is their ability to detect not only bacteria responsible for UTI but also the most common resistance to C3G antibiotics, the CTX-M group 1. The early diagnosis of this gene could lead to improving the antibiotic therapy and antimicrobial stewardship (Additional file 1 , Additional file 2 , Additional file 3 , Additional file 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the amplicons can be visualized by electrophoresis [ 137 ] and by monitoring the turbidity or the fluorescence. It is possible to look for color changes induced by chemical reaction [ 137 , 138 , 139 ]. The amplicons can be also detected using labelled primers with fluorescent dyes [ 140 ] or fluorescent intercalating dyes [ 137 ].…”
Section: Detection Of Amplicons By Lfiamentioning
confidence: 99%
“… Detection methods for amplicons; ( A ) Gel electrophoresis [ 137 ]; ( B ) Chemical reaction, visual inspection with fluorescence [ 137 ]; ( C ) Chemical reaction, visual inspection with color change [ 139 ]; ( D ) Fluorescent primers, fluorescence monitoring [ 140 ]; ( E ) Chemical reaction, in real-time, turbidity monitoring [ 138 ]. …”
Section: Figurementioning
confidence: 99%